Mapping Green Hydrogen and Renewable Energy Research in Extended BRICS (Brazil, Russia, India, China, South Africa and Others): A Bibliometric Approach with a Future Agenda - Benziane Roucham; Oussama Zaghdoud (Hydrogen)
Green hydrogen has emerged as a critical pillar of sustainable energy transitions, with its potential as a carbon-free fuel to decarbonize hard-to-electrify sectors while bolstering energy security. This study examines the trajectory of green hydrogen and renewable energy research within extended BRICS nations (the five core BRICS plus recent entrants) using bibliometric analysis, aiming to map publication trends, thematic focus, and collaborative networks from 2005 to 2024. A comprehensive dataset of 292 publications (2005–2024) was retrieved from Scopus. The results reveal a rapidly growing body of literature with an accelerating output in recent years and substantial citation impact. China leads in both publication volume and influence, followed by India and Russia, attesting to robust national research initiatives. Approximately one-quarter of the studies involve international co-authorship, underlining active collaboration among these countries and beyond. The novelty of this study lies in conducting the first comprehensive bibliometric analysis of green hydrogen and renewable energy research within the extended BRICS, highlighting publication trends, collaboration patterns, and thematic evolution to inform future research and policy development. These bibliometric insights offer valuable guidance for policymakers and industry stakeholders by highlighting core strengths (hydrogen production technologies) and pinpointing gaps where capacity-building is needed.